Estudo nutricional e sensorial de açúcares cristal, refinado, demerara e mascavo orgânicos e convencionais - Faria, Daiara Aparecida Mendes (2012)
This study aimed to evaluate the nutritional and sensory quality of different types of sugars, were analyzed for both the physico-chemical and sensory analyzes of eight samples of sugars including conventional and organic. The samples of sugars were analyzed for pH, moisture, polarization, amino acids, reducing sugar, conductivity ash, ICUMSA color, phenolics, turbidity, minerals and heavy metals. We used the Quantitative Descriptive Analysis (QDA) with 15 trained judges and 30 judges to evaluate the visual preference and 21 panelists for the preference, color and sweetness of orange juice sweetened with sugars under study. A study was made of the profile and consumer behavior in relation to sugars. The results showed that the brown sugar had lower levels of Pol, to the ash content samples of raw sugar and brown sugar D G values were higher than in relation to others; samples of organic sugars (D and G) were Ca and Fe greater than conventional. As the descriptive analysis, the aroma and sweet flavor and darker color were higher in organic samples. The schooling interfere with the visual preference and understanding of the concept of organic product and its cost and brand.